Determinants of conventional and contrast-enhanced ultrasound diagnosis of fat-poor angiomyolipoma <5 cm - Liang, Xia; Zeng, Xian-Tao; Hong, Zhi-Liang; Su, Miao-Jiao; Yang, Jian-Chuan; Wu, Song-Song (Frontiers in Oncology, 2024)
PurposeThis study aims to assess the diagnostic efficacy of conventional ultrasound (CUS) and contrast-enhanced ultrasound (CEUS) in detecting fat-poor angiomyolipomas(AML) with dimensions less than 5 cm. Additionally, the study seeks to identify independent indicators for predicting the presence of fat-poor AML.MethodsWe conducted a retrospective analysis of patients diagnosed with renal AML and renal cell carcinoma, who were admitted and underwent surgery at Fujian Provincial Hospital from January 2013 to October 2023. A total of 154 renal tumors were included (104 renal cell carcinomas and 50 fat-poor AMLs). Prior to radical or partial nephrectomy, these patients underwent both CUS and CEUS examinations. We systematically analyzed the features observed in CUS and CEUS, identified independent factors through multifactorial regression analysis, and evaluated diagnostic efficacy by calculating the area under the curve (AUC).ResultsUnivariate analysis revealed significant distinctions in fat-poor AML concerning gender, age, morphology, internal hyperechoic features (starry-sky sign, crescent sign), enhancement uniformity, and delayed enhancement, all displaying significance compared to renal cell carcinoma (RCC) (p < 0.05). Multivariate analysis demonstrated that internal hyperechoic features (p < 0.01, Odds Ratio [OR] = 0.003, 95% Confidence Interval [CI]: 0.000-0.0028) and enhancement uniformity (p < 0.01, OR = 0.016, 95% CI: 0.001-0.229) independently predicted fat-poor AML. The Receiver Operating Characteristic (ROC) curve’s area under the curve (AUC) for internal hyperechoic features (starry-sky sign, crescent sign) was 0.88 (95% CI: 0.80–0.95), with a sensitivity of 78.00%, specificity of 97.12%, positive predictive value of 92.85%, and negative predictive value of 90.18%. Conversely, the ROC curve AUC for enhancement uniformity was 0.70 (95% CI: 0.62–0.78), with a sensitivity of 96.00%, specificity of 44.23%, positive predictive value of 45.28%, and negative predictive value of 95.83%.ConclusionThis study suggests that both CUS and CEUS possess discriminative value in differentiating fat-poor AMLs from RCCs. Notably, internal hyperechoic features (starry-sky sign, crescent sign) and uniform enhancement within renal tumors emerge as potential independent indicators for predicting fat-poor AML.